Acute care for elders : a model for interdisciplinary care - Capezuti, Elizabeth A.; Palmer, Robert M.; Malone, Michael L. (Aging Medicine, 2014)
Acute Care for Elders (ACE) is a model of care designed to improve functional outcomes and to improve the processes for the care of older patients. This model includes: an environment of care designed to promote improved function for older patients; an interdisciplinary team that works together to identify/address the vulnerabilities of the older patients; nursing care plans for prevention of disability; early planning to help prepare the patient to return home; and a review of medical care to prevent iatrogenic illness. Acute Care for Elders: A Model for Interdisciplinary Care is an essential new resource aimed at assisting providers in developing and sustaining an ACE program. The interdisciplinary approach provides an introduction to the key vulnerabilities of older adults and defines the lessons learned from the Acute Care for Elders model. Expertly written chapters describe critical aspects of ACE: the interdisciplinary approach and the focus on function. The fundamental principles of ACE described in this book will further assist hospital leaders to develop, implement, sustain and disseminate the Acute Care for Elders model of care. Acute Care for Elders: A Model for Interdisciplinary Care is of great value to geriatricians, hospitalists, advance practice nurses, social workers and all others who provide high quality care to older patients.